THE DETERMINANTS OF INDIVIDUAL INTEREST TO BUY PRODUCT AT SHOPEE - Riezka Bening Dwifany (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
Online buying and selling are increasingly recognized by the public and e-commerce are growing rapidly. E-commerce, like Shopee, can facilitate buying and selling process more effective and efficient. This study aimed to examine consumer intention in using Shopee application to buy a product. This is a quantitative study and data were collected using a survey method, namely a questionnaire. The data of this study were analyzed using the Statistical Product and Service Solutions (SPSS). The respondents of this study were 400 undergraduate students of the Faculty of Economics and Business, Universitas Brawijaya. The results showed that performance expectancy, social influence, facilitating conditions, hedonic motivation, and habit have a positive effect on behavioral intention. However, effort expectancy and price value are found insignificant on behavioral intention. Thus, it can be concluded that the higher the performace expectancy, social influence, facilitating conditions, hedonic motivation, and habit, the higher the effect on consumer interest to buy a product at Shopee.Keywords: Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, Habit, Behavioral Intention, Shopee.